Economic returns of one versus two fungicide applications in oklahoma winter wheat. Issue 1 (9th March 2020) - Watson, Branden H.; Hunger, Robert M.; Marburger, David A.
Abstract: Fungicides protect winter wheat ( Triticum aestivum L.) yield potential by managing foliar fungal diseases, but little information comparing one vs. two applications is available for the US southern Great Plains. Field experiments conducted from 2016–2018 at two Oklahoma locations (Apache and Stillwater) used two winter wheat cultivars ('Gallagher' and 'Bentley') and four fungicide application timings (control, Feekes 6, Feekes 9, and Feekes 6 + 9). Disease levels were highest during 2017 due to leaf rust. Dry conditions during 2018 limited disease development overall. Fungicide applications resulted in significantly higher yields in three of eight year × location × cultivar comparisons, all during 2017. The Feekes 6 + 9 treatment only showed the highest grain yield for the leaf rust‐susceptible cultivar Bentley at Stillwater that season. Partial profit was also examined by year, location, and cultivar using four fungicide cost scenarios at three grain sale prices. Only 22 of 96 comparisons showed significant positive partial profit from fungicide use, and all occurred at Stillwater during 2017. Two fungicide applications had the highest profit in 4 of the 22 comparisons for the cultivar Bentley. However, a single application of a low‐cost fungicide was most often among the highest profitable fungicide treatments, depending when higher disease levels were present. Partial profits from one and two fungicide applications were not significant or significantly negative when disease levels were low. Knowledge of cultivar disease susceptibility and disease scouting need to be considered to economically justify one or two fungicide applications in Oklahoma winter wheat.